DEVELOPMENT OF A MULTI-FACTOR MATHEMATICAL MODEL TO EVALUATE THE EFFICIENCY OF AGRICULTURAL LAND USE - Natalya O. Gordeeva (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article discusses the development process and the possibility of multifactor model use to model the cadastral value of agricultural land on the example of the Belgorod region. The structure of a multifactor model is proposed and they performed the quantitative analysis of factors affecting the cadastral value of agricultural lands.